Effects of Grain Boundary Engineering on the Microstructure and Corrosion Fatigue Properties of 316L Austenitic Stainless Steel - Zhang, Mingxian; Zhang, Chenxin; Wu, Huanchun; Yang, Bin (Frontiers in Materials, 2022)
Grain boundary engineering (GBE) treatment was performed through thermo-mechanical processing (TMP) to optimize the grain boundary character distribution (GBCD) of 316L austenitic stainless steel. The effects of TMP on the GBCD and corrosion fatigue properties in high-temperature and high-pressure water were investigated. The results indicated that a high fraction (about 74%) of special boundaries as well as the interrupted network of random high-angle grain boundaries were obtained through the 5% strain followed by annealing at 1273 K for 90 min. The Σ9 and Σ27 boundaries were generated by the reaction of special boundaries. The highest corrosion fatigue life for 3187 cycles was obtained when the TMP parameters of the 316L ASS were strain of 5%, annealing temperature of 1273 K and annealing time of 45 min. The low energy special boundaries had strong intergranular corrosion resistance, but the strength of these boundaries was not enough to resist the propagation of transgranular fatigue cracks.